Varietal Diffusion in Marginal Seed Systems: Participatory Trials Initiate Change in East Timor - Lacoste, Myrtille; Williams, R.; Erskine, W.; Nesbitt, H.; Pereira, L.; Marçal, A. (2012)
Participatory on-farm trials of introduced varieties of the major staple crops were implemented in East Timor to contribute to addressing chronic national food insecurity. This paper confirmed the suitability of the participatory varietal selection approach by measuring high early adoption (over 80% one year after the trials). Three years on, significant areas of the new varieties were managed by adopters, and planting material from a third of the trials had been shared with an average of five non-participating households. However, crop failures (particularly from climatic hazards and animal damage) and the loss of planting material were common, reducing subsequent diffusion with crop characteristics and the availability of planting material playing critical roles. The study showed that on-farm testing was key as a first-stage mechanism in marginal areas but insufficient alone to achieve permanent varietal insertion in these particularly isolated farmers' seed systems. To ensure long-term adoption and broad diffusion, it is essential to combine the approach with comprehensive, flexible and reliable planting material sources. Linking the formal and existing farmers' seed systems at the community level appears to be the most promising option. The study also demonstrated that small, well-defined surveys can be critical, cost-efficient tools to monitor technology diffusion in resource-poor areas. © 2012 Copyright Taylor and Francis Group, LLC.